Reduction of CO2 with KBH4 in solvent-free conditions. (24th August 2016) - Picasso, Carolina V.; Safin, Damir A.; Dovgaliuk, Iurii; Devred, François; Debecker, Damien; Li, Hai-Wen; Proost, Joris; Filinchuk, Yaroslav
Abstract: Metal hydrides have been commonly used as reducing agents in organic and inorganic chemistry. Until today, the capability of potassium borohydride (KBH4 ) to reduce aldehydes and ketones to alcohols has been known for its advantage of high stability on air and in alkaline solutions. Conversion of CO2 to formates and boron methoxide compounds by metal borohydrides has been recently studied. In this work we investigated the solid–gas non-catalytic reaction between KBH4 and CO2 under both mechanochemical and thermal-induced conditions with the simultaneous formation of potassium formylhydroborates, K[H x B(OCHO)4 − x ] ( x = 1–3), as main products. The first crystal structure of a product of solid–gas metal borohydride – CO2 reaction, potassium triformylhydroborate, K[HB(OCHO)3 ], obtained mechanochemically, was elucidated. The evolution of the reaction between solid KBH4 and CO2 was monitored by a combination of thermogravimetric analysis coupled with mass spectrometry and infrared spectroscopy from room temperature to 500 °C, revealing the generation of hydrogen, methanol and carbon monoxide in a three-step mass increase reaction. Variable temperature in situ synchrotron X-ray powder diffraction under CO2 pressure revealed the formation of a new crystalline intermediate phase with an unidentified composition but crystallizing in a monoclinic space group, and KBO2 during the second and third steps, respectively. Gas chromatography of evolving species under CO2 flow revealed for the first time the formation of methanol and methane in water-free conditions. Highlights: Solid-gas non-catalytic reaction between KBH4 and CO2 was studied under mechanochemical and thermal-induced conditions. Potassium formylhydroborates, K[H x B(OCHO)4– x ] ( x = 1–3), are the main products. Crystal structure of potassium triformylhydroborate K[HB(OCHO)3 ], obtained mechanochemically, was elucidated. MS and FTIR reveal the generation of hydrogen, methanol and carbon monoxide. Gas chromatography reveals for the first time the formation of methanol and methane in water-free conditions.